Evaluation of the antigen-antibody complex vaccine of Gumboro disease administered in ovo in broiler chickens challenged with F52/70 strain - Guzmán G., John (2010)
The objective of the study was to evaluate the protection and safety for in ovo vaccination against Infection Bursal Disease. Cobb Vantress broilers of one day of age (n=450) were distributed in three groups: Group A, vaccinated at 9 and 19 days with two commercial live vaccines containing Lukert and 2512 strains, respectively; group B, vaccinated in ovo with the antigen-antibody complex at 18 days of incubation; and group C, unvaccinated. At 35 days of age, 20 birds from each group were challenged, ocular via, with the F52/70 strain of Gumboro disease. The security of the complex vaccine was evaluated weekly until 47 days of age by determining the bursal index, gross lesions, histopathological lesions of the bursa, and serological response. Group B showed the best protection with 75% as compared with groups A (68%) and C (30%). Injuries after challenge were characterized by swelling, bleeding, and petechiae in the bursa. In non-challenged birds were none significant differences between groups A and B for the index and bursal histopathology lesions until 28 days of age; however, group A differed from groups B and C at 35 days of age (p<0.05). At the end of the study, group A had 1948 and 2047 antibodies titers higher than groups B and control respectively.